Phytochemical Analysis of Stem and Leaf Extracts of Jasminum sambac (L.) Aiton by FTIR Method: Analysis of Stem and Leaf of Jasminum sambac (L.) - Rizwana Rafique; Zaheer Uddin Khan; Muhammad Ameer Nawaz Akram; Kanwal Javid; Sundas Iltaf; Memoona Shaukat; Hafsa Shaukat; Shaukat Ali (Biological Sciences - PJSIR, 2023)
Plants with the help of secondary metabolites release their stress as well as act like protective substances from toxicity. FTIR (Fourier Transform Infrared Spectroscopy) was considered as a scientific procedure with a high determination that used to distinguish the constituents of compounds and their structures. Spectroscopy was used to check the presence of secondary metabolites in the plants, which is due to valuable data based on composition, quantitative and subjective pattern related to biomolecules was achieved. The analysis of phytochemicals of stem and leaf of Jasminum sambac (L.) Aiton (n-hexane, chloroform, ethanol and aqueous) extracts demonstrated that the tannins, saponins, flavonoids, alkaloids and reducing sugars were present in all extracts but the presence of chemicals varied in each extract and the presence of these phytochemicals was confirmed by FTIR analysis. The chemical compounds present in Jasminum sambac (L.) Aiton were observed very effective as antimicrobial and antioxidant agents.